Tarenna thorelii (Rubiaceae), a new record for Thailand - Kesonbua, Wirot; Chantaranothai, Pranom (Thai Forest Bulletin (Botany), 2023)
Tarenna thorelii is reported as a new record for Thailand based on collections from Khon Kaen and Roi Et Provinces. A morphological description based on Thai specimens, distribution, ecological information, conservation status, and short notes on the species as well as an illustration are provided. In addition, a lectotype for T. thorelii is proposed.